Synthesis of Cyclopentanone and Cyclohexanone Derivatives - Ali, Nowara; Abdullah Gheath; Abdalhamid Alarafi (AlQalam Journal of Medical and Applied Sciences, 2025)
A series of compounds (I–XIII) were synthesized by reacting ethyl 2-oxocyclopentane-1-carboxylate (1) or ethyl 2-oxocyclohexane-1-carboxylate (2) with various diamines, including ethane-1,2-diamine, benzene-1,4-diamine, hydrazine hydrate, benzidine, N¹, N³-bis(2-aminoethyl) malonamide, 3-hydroxyaniline, malonohydrazide, and piperazine. Most derivatives (I, II, III, VI, VII, VIII, X, XIII) adopted enamine structures via a 2:1 reaction ratio, whereas compounds IX and XI exhibited distinct structural frameworks due to a 1:1 reaction pathway. Notably, the reaction of β-keto ester 1 with hydrazine hydrate yielded enamine III as a minor product and pyrazolone IV as the major derivative, while the analogous reaction with compound (2) exclusively produced pyrazolone V. Additionally, the reaction of compound (2) with malonohydrazide afforded an azine derivative (XII). All syntheses proceeded under mild conditions with moderate yields, and the structures were characterized using melting point, TLC, IR, MS, ¹H-NMR (with D₂O exchange), ¹³C-NMR, and APT analyses. Preliminary screening revealed antimicrobial activity in selected derivatives.